Інформаційне забезпечення управління кадровим потенціалом аграрних підприємств - Вініченко, Ігор Іванович; Vinichenko, Igor; Дьяченко, Ніна Костянтинівна; Diachenko, Nina; Лапа, Вероніка Олегівна; Lapa, Veronica (Дніпровський державний аграрно-економічний університет, 2021)
У статті розглянуто основні тенденції використання інформаційно-комунікаційних технологій в контексті управління кадровим потенціалом аграрних підприємств. Встановлено, що інноваційний розвиток аграрної сфери країни залежить від швидкості оновлення техніко-технологічних та інформаційних знань, а також рівня розвитку динамічних здібностей сільськогосподарських працівників. Розглянуто інформаційні технології, що використовуються в аграрному виробництві під час управління трудовими ресурсами, маркетингом, виробництвом. Зазначено на необхідності проведення систематичних досліджень щодо розвитку цифрової трансформації в агробізнесі з економічним обгрунтуванням доцільності впровадження діджиталізації до HR-менеджменту аграрних підприємств. Зроблено висновок, що інформаційне забезпечення управління аграрним кадровим потенціалом має грунтуватися на новітніх знаннях та впроваджуватися у бізнес- та HR-процесах менеджменту сільськогосподарських підприємств. The article considers the main trends in the use of information communication technologies in the context of human resources management of agricultural enterprises. The relevance of the introduction of innovation and information is indicated technologies in the HR-management system on the basis of business and HR optimization processes of agricultural enterprises. It is established that the innovative development of the agricultural sector of the country depends on the speed of updating technical and technological and information knowledge, as well as the level of development of dynamic agricultural abilities employees. The need for professional development has been identified level of employees, systematic updating of knowledge, skills, abilities computer skills. The information technologies used in agrarian are considered production. It is established that the general functionality of applications of HRM-systems expand by — adding opportunities for group work and more perfect work with content and analytics, automatic synchronization the terms of the contract of employees with the actual results of their work, distribution of the Internet for hiring staff, etc. The functionality of HR management information systems allows effectively carry out personnel planning, hiring, certification, personnel reserve, training, work motivation. The need for an integrated partnership with IT companies is proved, research institutions and educational institutions for the purpose dissemination of the best information technologies in agricultural production and formation of a single information space of agribusiness. The need for professional development has been identified level of employees, systematic updating of knowledge, skills, abilities computer skills. The need for systematic research on development of digital transformation in agribusiness with economic substantiation of expediency of introduction of digitalization to HR-management of agricultural enterprises. It is concluded that information management agricultural human resources should be based on the latest knowledge and to be implemented in business and HR-management processes agricultural enterprises.
Information provision of human resources in the management
Keywords: кадровий потенціал; human resources; інформаційні технології; information technology; аграрні підприємства; agricultural enterprises